Whole genome sequencing analysis of cognitively Wellderly individuals identifies potential protective genetic variants for Alzheimer's disease. (December 2021) - Peloso, Gina M; Rosser, Morgan A; Bis, Josh C; Fornage, Myriam; Boerwinkle, Eric; Satizabal, Claudia L; Psaty, Bruce M.; Lopez, Oscar L.; Mosley, Thomas H; Wang, Yanbing; Dupuis, Josée; Destefano, Anita L.; et al.
Abstract: Background: Genetic variants that confer protection from Alzheimer's disease (AD) may be particularly critical in developing therapeutics. To target protective variant identification, we performed genetic association testing among selected individuals with whole genome sequencing (WGS) that remained alive and dementia‐free beyond age 85 ("Wellderly"). Methods: We selected 1, 873 White and Black Wellderly individuals with documented normal cognition beyond age 85 as determined by direct, in‐person assessment from three cohorts (FHS, CHS, and ARIC) with WGS from the NHLBI TOPMed project. We used two sets of comparison groups from these three cohorts: (i) general controls, non‐Wellderly individuals including persons without and with dementia [n=8, 502] and (ii) individuals who developed dementia before age 85 [n=810]. We performed generalized mixed model regression for binary outcomes using Wellderly status, separately with each comparison group, for each variant with a minor allele frequency (MAF) > 1%, adjusting for study and principal components of ancestry as fixed effects, and a genetic‐relatedness matrix as a random effect to account for relatedness and shared ancestry. Additionally, we performed association testing adjusting for APOE e4 status. Our top results outside of the APOE locus tended to be more significant after adjusting for APOE e4 status. Results: We observed a reduced risk of Wellderly status compared to general controls at the APOE locus (rs429358, MAF=14%, odds ratio [OR] = ‐0.40, p=1.6x10 ‐10 ), consistent with the known association of the APOE locus with dementia. Additionally, we found suggestive associations at CACNA2D3 (rs73085981, MAF=16%, OR=1.44, p=6.7x10 ‐8 ), ASTN2 (rs7350805, MAF=1%, OR=1.10, p=4.3x10 ‐7 ), and YEATS4 (rs167588, MAF=1%, OR=1.1, p=3.7x10 ‐7 ) using the general controls adjusting for APOE e4 status. CACNA2D3 and ASTN2 have plausible biological connections to AD. CACNA2D3 is a calcium channel gene and rare copy number variation has been implicated in voltage gate calcium channel genes in individuals with late‐onset AD. ASTN2 encodes a protein that is expressed in the brain and may function in neuronal migration, and has been previously implicated in age of onset of AD and is associated with hippocampal volume. Conclusion: Although only variants in the APOE locus reached a genome‐wide significance threshold, we found suggestive associations for Wellderly status with biological plausibility.